Controlled rotation of long bones by guided growth: A proof of concept study of a novel plate in cadavers. Issue 5 (9th August 2021) - Abood, Ahmed A.; Hellfritzsch, Michel Bach; Møller‐Madsen, Bjarne; Brüel, Annemarie; Westersø, Thomas Søndergaard; Vedel‐Smith, Nikolaj Kjelgaard; Rahbek, Ole; Rölfing, Jan Duedal
Abstract: Our novel plate design has been developed for controlled rotation of long bones by guided growth. The objective of this proof‐of‐concept study was to evaluate the precision of the rotation in the femur. Twelve cadaverous femora of six adults (right = 6, left = 6) underwent an osteotomy at the level of the physeal scar. The plates were inserted on each side of the distal femur. Growth was simulated by axial distraction of the bone segments. The femur was stabilized using a unilateral external fixator. Femoral torsion was assessed with computed tomography (CT) and with an electric goniometer before and after distraction. The obtained rotation was compared to the predicted rotation based on the dimension of the plate and the bone. All femora were rotated as intended. The mean obtained rotation was 26.3° (95% confidence interval [CI]: 23.5–29.0) and the mean predicted rotation was 28.2° (95% CI: 26.9–29.5) ( p  > 0.82). The mean axial distraction was 19.5 mm (95% CI: 17.7–21.3). The predicted rotation of the femora was similar to the obtained values on CT and by goniometer. The obtained rotation occurred as a result of an axial distraction of approximately 2 cm. This suggests a potential for controlled rotation of the femur based on the circumference of the bone and plate dimensions that occurs simultaneously with axial distraction. Clinical significance: These findings suggest a possible clinical application in the treatment of maltorsion in children by guided growth, where theplate design guides the bone into torsional axial growth correcting the deformity.